Plan de negocios para la creación de empresa comercializadora y productora de calzado tipo tacón desmontable por medio de maquila en la ciudad de Armenia Quindío. (2014)
In the national market of the feminine footwear has been showing diverse changes driven by world fashion tendencies, this had been setting development of new designs and styles with new characteristics that impulses the wish of women to buy. 2 Footwear with hills gives women fancy personal presentation. However, it also generates second effects by prolonged use provoking uncomfortable use affecting health seriously. As the new illness generation of kidneys, it seems that it also affects the column and feet. In the previous base, we could identify a business opportunity in the feminine hills footwear area nationally, especially in Armenia city. For this reason the development has been carried out by the present business plan , which presents this financing study, technical, organizational, juridical, environmental and of the market; searching to generate fundaments and bases for the creation of the company.